Designing Theoretical and Conceptual Framework for Evaluation of Education Curriculum (Xi-Xii) Using CIPP Model in Pakistan - Asma, Shahzadi; Khan, Fahad Hameed (2024)
At the heart of any significant research endeavor lies the theoretical and conceptual framework, which serves as the guiding structure that shapes the study's objectives, methodology, and overall approach. By connecting research data back to the concepts and relationships outlined in the framework, researcher can derive meaningful insights and draw informed conclusions. The purpose of the curriculum evaluation is to assess the strengths and shortcomings of an existing curriculum so that improvements in curriculum design or content can be made. This, however, has not been the case in the Pakistani context and curricula often remain static for extended periods. This research aims to examine the curriculum of Education subject by designing theoretical framework applying the curriculum evaluation models. It helps to understand the evaluation procedure by developing the conceptual framework using the CIPP (Context, Input, Process, and Product) evaluation model developed by Stufflebeam (1971). The discussion highlights the significance of theoretical and conceptual framework in curriculum evaluation and researchers would be able to design these frameworks in social sciences. The findings would be beneficial for novice investigators in taking steps for selecting appropriate theoretical framework that will help to proceed the steps in curriculum evaluation and designing the conceptual framework.